Developing English Learning Application Model for Vocational High School Students - Taufan, Gullit Tornado; Suharsono, Degita Danur; Kamal, Mushthofa (Politeknik Negeri Jember, 2024)
This is a research and development (R&D) with the aim of developing a vocational-themed English application model for SMK in Jember. There were three steps carried out to complete this study including categorizing the areas of expertise offered at State Vocational Schools (SMKN) in Jember, analyzing the use of information technology in learning English at SMKN in Jember by distributing questionnaire to the English teachers and interview, and designing a vocational-themed English learning application model. The result of the study is a model of an Android-based application for English learning specific for SMK under seven vocational expertise fields covering four English skills and two components. Those are reading, listening, writing, and speaking. Moreover, the application also covers grammar and vocabulary materials specific for SMK students. The application model is the basis of developing the prototype of the vocational-themed English learning application. From the model, an English learning application which is specifically designed for students of vocational high schools can be created based on 7 areas of expertise, as found through the study, including: 1) Technology and Engineering, 2) Information and Communication Technology, 3) Agribusiness and Agro-technology, 4) Maritime Affairs, 5) Business and Management, 6) Tourism, and 7) Arts and Creative Industries.